2021
DOI: 10.34069/ai/2021.48.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Social media projects for boosting intercultural communication by means of learning English

Abstract: The paper is targeted to explore the intensification of communication among culturally diverse students by means of creating social media groups. In frames of the psycholinguistic experiment, Ukrainian and Chinese students were working together at detecting common, similar and distinct features in idioms from the Ukrainian, English and Chinese languages. They intented to decode the phraseological picture of the world of Ukrainian, English and Chinese. Participation in social media group enabled participants’ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These thirty articles revealed that there are five groups of targeted subjects that are of interest to researchers. A significant sum of studies was performed on the tertiary education level learners with 19 articles contributing to the list [30,31,35,36,[38][39][40]43,45,46,[48][49][50][51][52][53][54][55]58]. Five articles were directed towards the response from educators [33,34,42,56,57].…”
Section: N/a /mentioning
confidence: 99%
See 4 more Smart Citations
“…These thirty articles revealed that there are five groups of targeted subjects that are of interest to researchers. A significant sum of studies was performed on the tertiary education level learners with 19 articles contributing to the list [30,31,35,36,[38][39][40]43,45,46,[48][49][50][51][52][53][54][55]58]. Five articles were directed towards the response from educators [33,34,42,56,57].…”
Section: N/a /mentioning
confidence: 99%
“…Based on Table 4 below, it can be deduced that Facebook has received the most attention as a single SNS platform to determine the efficacy of SNS in English language learning. Five articles [36,38,41,49,50] have researched the assimilation of Facebook in formal English learning whereas only one article [42] employed Facebook for informal English learning. About a third of the total articles reviewed [29,35,37,39,40,45,46,48,[51][52][53]57] have not specified any SNS platform in the research, indicating that a lot of studies were done to investigate the influence of SNS as a whole on learning rather than just a single platform.…”
Section: Rq 1: What Are the Types Of Social Networking Sites (Sns) Pl...mentioning
confidence: 99%
See 3 more Smart Citations